MITOS KEBUDAYAAN JAWA DALAM NOVEL DELUSI KARYA SUPAAT I. LATHIEF (KAJIAN ANTROPOLOGI SASTRA) - Aris Nurhuda (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2023)
This study aims to find out how the beliefs that exist in Javanese culture towards the myths depicted in the novel Delusi by Supaat I. Lathief. The research design uses a qualitative descriptive method, namely to describe the contents of the novel in accordance with previously identified aspects such as customs in the past, traditions, and belief in myths. This research study technique uses library techniques, namely by studying books related to the problem to be studied. Researchers get data that begins with reading activities, studying, then grouping the data obtained. After all the data is collected then analyze and describe the data based on the aspects studied.Based on the results of a study of the depiction of the novel Delusi about the understanding or mindset of the Javanese people about the myth about the existence of a belief system depicted in the novel Delusi by Supaat I. Lathief (an anthropological study of literature) that most Javanese people believe in the myths that develop in their village. Most of the villagers still adhere to a belief system in the existence of spirits that inhabit objects and give offerings with the aim of calming the village. Residents also believe that begging at the tomb can bring abundant sustenance. Events that occur are caused by the existence of a belief system in the existence of myths about safety, abundant sustenance, and success in harvests when one realizes that it is the result of one's own efforts and the will of the Almighty God, not from what they have believed so far on things which is mystical.Keywords: myth, Javanese culture, literary anthropology